The Effect of Satisfaction and Trust on Purchase Intention on Aromania Parfumery Kapuas Products, Bengkulu City - Riri Astuti; Khairul Bahrun (Journal of Indonesian Management, 2022)
Aromania Parfumery is a distributor of imported and local perfumes/perfumes, both wholesale and retail, which has dozens of outlets spread throughout Indonesia. The packaging provided by Aromania Parfumery is 500 ml, 250 ml, 100 ml and 50 ml and provides refill/refill perfume. This study aims to determine how much influence satisfaction and trust have on purchase intention on Aromania Parfumery Kapuas products, Bengkulu City. In this study, data were obtained through observation and distributing questionnaires to 100 people who were used as respondents, namely consumers who bought products at Aromania Parfumery Kapuas, Bengkulu City. Then the data analysis was carried out using quantitative data. Quantitative analysis includes instrument testing, Classical Assumption Test, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing. The results of this study can be seen from the multiple linear regression test using the SPSS program, namely Y = 5.504 + 0.362 (X1) + 0.513 (X2). The results of the coefficient of determination (R2) the value of R Square is 0.595 or 59.5%, where the coefficient of determination means that together the satisfaction and trust variables contribute to influencing purchase intention at Aromania Parfumery Kapuas Bengkulu City, while the rest is 0.405 or 40.5% is influenced by other variables outside the study which were not examined in this study. Testing the hypothesis using the t test and F test shows that the satisfaction (X1) and trust (X2) variables have a significant effect on purchase intention (Y), where the tcount value is greater than the ttable value, and the Fcount value is greater than the Ftable value. This means that Ho is rejected, Ha is accepted.